Transformed Calculation Models in Practice of Dynamic Analysis of Fixed Offshore Platform Structures - Valerii I. Sutyrin; Elvira R. Kuzhakhmetova (Structural Mechanics of Engineering Constructions and Buildings)
In this study, an attempt is made to study the nature of changes in the characteristics of the stress-strain state (SSS) of a fixed offshore platform structure under the influence of seismic loads. The structure is installed on a truss-type support base and is fixed in operating position by steel tubular piles driven into the soil base through support columns (deep foundation). A combined 3D finite element model “Superstructure - Pile Foundation - Soil Base” was used as the research tool. The purpose of the study was to develop a methodology for analyzing the dynamics of a fixed offshore platform as a 3D mechanical model, the finite element model of which is characterized by a large number of degrees of freedom. The efficiency of the numerical analysis of the system is increased by constructing a transformed calculation model (TCM). The transformation involves the transition to contour and calculation super nodes located along the axis of symmetry of the foundation pile. Contour nodes are used to connect the Substructure of super nodes to the Superstructure. The calculation nodes allow to take into account the vibrations of the pile foundation in the soil base. An algebraic computational procedure is proposed that allows the formation of matrices of generalized stiffness and mass coefficients. Modal analysis using a transformed calculation model (TCM) provides a significant reduction in the order and total computational time of the mechanical system. The possibility of analyzing dynamic reactions by a direct method based on the accelerogram of a real earthquake is provided.